Response timescales of the magnetotail current sheet during a geomagnetic storm: Global MHD simulations - Eggington, J. W. B.; Coxon, J. C.; Shore, R. M.; Desai, R. T.; Mejnertsen, L.; Chittenden, J. P.; Eastwood, J. P. (Frontiers in Astronomy and Space Sciences, 2022)
The response of the Earth’s magnetotail current sheet to the external solar wind driver is highly time-dependent and asymmetric. For example, the current sheet twists in response to variations in the By component of the interplanetary magnetic field (IMF), and is hinged by the dipole tilt. Understanding the timescales over which these asymmetries manifest is of particular importance during geomagnetic storms when the dynamics of the tail control substorm activity. To investigate this, we use the Gorgon MHD model to simulate a geomagnetic storm which commenced on 3 May 2014, and was host to multiple By and Bz reversals and a prolonged period of southward IMF driving. We find that the twisting of the current sheet is well-correlated to IMF By throughout the event, with the angle of rotation increasing linearly with downtail distance and being more pronounced when the tail contains less open flux. During periods of southward IMF the twisting of the central current sheet responds most strongly at a timelag of ∼ 100 min for distances beyond 20 RE, consistent with the 1–2 h convection timescale identified in the open flux content. Under predominantly northward IMF the response of the twisting is bimodal, with the strongest correlations between 15 and 40 RE downtail being at a shorter timescale of ∼ 30 min consistent with that estimated for induced By due to wave propagation, compared to a longer timescale of ∼ 3 h further downtail again attributed to convection. This indicates that asymmetries in the magnetotail communicated by IMF By are influenced mostly by global convection during strong solar wind driving, but that more prompt induced By effects can dominate in the near-Earth tail and during periods of weaker driving. These results provide new insight into the characteristic timescales of solar wind-magnetosphere-ionosphere coupling.